The qualifying study of metaphor as a vehicle of frame in the news texts about 11-m terrorist attacks (El País, The Guardian and Izvestia) - Mukhortikova, Tatiana (2018)
This article includes the study of metaphor as a strategy for interpreting the terrorist attacks perpetrated in Madrid on March 11, 2004 in three newspapers published in different languages in different countries. The text offers a multidisciplinary view to the metaphor, based on the interpretation of this figure as one of the linguistic forms of the interpretation of reality in a journalistic text and the so-called framing theory.